2019
DOI: 10.2196/12554
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Depression: Social Network Analysis and Random Forest Techniques

Abstract: Background Major depressive disorder (MDD) or depression is among the most prevalent psychiatric disorders, affecting more than 300 million people globally. Early detection is critical for rapid intervention, which can potentially reduce the escalation of the disorder. Objective This study used data from social media networks to explore various methods of early detection of MDDs based on machine learning. We performed a thorough analysis of the dataset to characterize t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(76 citation statements)
references
References 37 publications
0
75
0
1
Order By: Relevance
“…Demand-based infoveillance studies using internet search queries have primarily focused on predicting infectious disease outbreaks, such as Zika, influenza, dengue, and the measles virus [ 17 - 19 ]. Other studies analyzed user’s behavior on social media and proposed a model that was based on machine learning for the early detection of depression and suicidal risk [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demand-based infoveillance studies using internet search queries have primarily focused on predicting infectious disease outbreaks, such as Zika, influenza, dengue, and the measles virus [ 17 - 19 ]. Other studies analyzed user’s behavior on social media and proposed a model that was based on machine learning for the early detection of depression and suicidal risk [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The idea that depression is associated with changes in language is supported by previous research. Specifically, it has been shown that individuals with depression more frequently use a variety of terms that describe negative emotions [19][20][21] , first-person pronouns (FPPs) [21][22][23][24][25] , common symptoms 26 and linguistic inquiry and word count (LIWC) categories deemed to correspond to 'absolutist' language 27 . Machine learning approaches have shown good performance with respect to predicting whether social media users have depression [28][29][30] , identifying the most useful term features to render a prediction.…”
mentioning
confidence: 99%
“…These criteria map and measure the links among things (i.e., people-people, people-item, item-item, and so on). SNA is a process of analyzing the social structures through the joint use of networks and GT [119][120][121]. SNA characterizes networked structures represented as graph, where nodes (individual actors, users, or things within a network) and the edges/links (relationships or interactions) that connect these nodes [122].…”
Section: Social Network Analysis Via Graphsmentioning
confidence: 99%